Hemodynamic alternations following stent deployment and post-dilation in a heavily calcified coronary artery: In silico and ex-vivo approaches. (December 2021) - Gamage, Peshala T.; Dong, Pengfei; Lee, Juhwan; Gharaibeh, Yazan; Zimin, Vladislav N.; Dallan, Luis A.P.; Bezerra, Hiram G.; Wilson, David L.; Gu, Linxia
Abstract: In this work, hemodynamic alterations in a patient-specific, heavily calcified coronary artery following stent deployment and post-dilations are quantified using in silico and ex-vivo approaches. Three-dimensional artery models were reconstructed from OCT images. Stent deployment and post-dilation with various inflation pressures were performed through both the finite element method (FEM) and ex vivo experiments. Results from FEM agreed very well with the ex-vivo measurements, interms of lumen areas, stent underexpansion, and strut malapposition. In addition, computational fluid dynamics (CFD) simulations were performed to delineate the hemodynamic alterations after stent deployment and post-dilations. A pressure time history at the inlet and a lumped parameter model (LPM) at the outlet were adopted to mimic the aortic pressure and the distal arterial tree, respectively. The pressure drop across the lesion, pertaining to the clinical measure of instantaneous wave-free flow ratio (iFR), was investigated. Results have shown that post-dilations are necessary for the lumen gain as well as the hemodynamic restoration towards hemostasis. Malapposed struts induced much higher shear rate, flow disturbances and lower time-averaged wall shear stress (TAWSS) around struts. Post-dilations mitigated the strut malapposition, and thus the shear rate. Moreover, stenting induced larger area of low TAWSS (<0.4 Pa) and lager volume of high shear rate (>2000 s −1 ), indicating higher risks of in-stent restenosis (ISR) and stent thrombosis (ST), respectively. Oscillatory shear index (OSI) and relative residence time (RRT) indicated the wall regions more prone to ISR are located near the malapposed stent struts. Highlights: CFD, integrated with FEM, were adopted to study the hemodynamic alternations following stenting and post-dilations. Pulsatile blood flow is modeled in CFD simulation by employing a Windkessel type boundary condition at the distal end. The iFR analysis demonstrated the efficacy of post-dilations in a heavily calcified coronary artery. TAWSS, OSI, and RRT indicated atherogenic hemodynamic conditions on the wall regions located near the malapposed stent struts.